Evidence‐Based Practice in a Global Context. (March 2015) - Cardemil, Esteban V.
Abstract : This commentary examines how the adoption of benchmarking can promote the internationalization of evidence‐based practice. Given the increasing evidence documenting the role of culture and context in the shaping of experiences and expressions of distress, as well as influencing attitudes and conceptions of mental health services, benchmarking may not represent the best approach to addressing global public health agendas. A brief overview of the sequential approach to developing, evaluating, and disseminating treatments in novel cultural contexts is presented, in which benchmarking can play an important, albeit secondary role. It is argued that in a global context, benchmarking's role may better function to promote dissemination within particular contexts, rather than between them.